2021
DOI: 10.21203/rs.3.rs-828351/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the external exposome of South African children using wearable passive samplers and high-resolution mass spectrometry

Abstract: Children in low- and middle-income countries are often exposed to higher levels of, and more vulnerable to, the health effects of air pollution. Little is known about the diversity, toxicity, and dynamics of airborne chemical exposures at the molecular level. We developed a workflow employing state-of-the-art wearable passive sampling technology coupled with high-resolution mass spectrometry to comprehensively measure 147 children’s personal exposures to airborne chemicals in Limpopo, South Africa, as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…A few of the reviewed studies point out the health risks of herbicides (e.g., glyphosate [ 35 ]) and fungicides (e.g., mancozeb [ 24 ]). Most studies focused on the one-exposure one-disease approach, taking into account only single effects of pesticides, while several studies investigating use [ 66 , 67 , 68 ], environmental occurrence [ 56 , 69 , 70 , 71 , 72 ], and human exposure [ 49 , 73 , 74 , 75 ] showed that exposure happens from multiple pesticides over time, which could potentially result in cumulative and synergistic environmental [ 21 ] and public health effects [ 24 , 35 ]. The missing research on multiple pesticides could be due to the challenges with analyzing these pesticides in local laboratories [ 76 , 77 ] and knowledge gaps with data analysis techniques [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few of the reviewed studies point out the health risks of herbicides (e.g., glyphosate [ 35 ]) and fungicides (e.g., mancozeb [ 24 ]). Most studies focused on the one-exposure one-disease approach, taking into account only single effects of pesticides, while several studies investigating use [ 66 , 67 , 68 ], environmental occurrence [ 56 , 69 , 70 , 71 , 72 ], and human exposure [ 49 , 73 , 74 , 75 ] showed that exposure happens from multiple pesticides over time, which could potentially result in cumulative and synergistic environmental [ 21 ] and public health effects [ 24 , 35 ]. The missing research on multiple pesticides could be due to the challenges with analyzing these pesticides in local laboratories [ 76 , 77 ] and knowledge gaps with data analysis techniques [ 35 ].…”
Section: Discussionmentioning
confidence: 99%